Rethinking the Enlightenment - Elkana, Yehuda (Approaching Religion, 2011)
In this introductory statement, given at the beginning of the Aboagora symposium in Turku in August 2011, Yehuda Elkana highlights the need, in accordance with the title of the conference, to rethink rather than unthink the Enlightenment. Indeed, the Enlightenment remained an unfinished project, but one should never forget that this era formed the basis for the greatest and most important creation of knowledge in all areas for 300 years. Over the last 100 or more years, however, cracks have started to appear in this edifice, Elkana argues: researchers have started to realise that one cannot really distinguish the rational from the irrational and that being contextual does not necessarily mean being relativist.